Spatial variation of concentration of particulate matter in Junin and Amazonia of Brazil - Angeles Suazo, Julio Miguel (2023)
Atmospheric particles (PM10 and PM2.5) are responsible for serious problems in human health. Therefore, this study determined the spatial variation of the concentration of particulate matter in the department of Junin, as in the Brazilian Amazon for the period 2021. The data obtained were analyzed using the low-cost PA-II Purpleair sensor, to measurements of particulate matter (PM1, PM2.5 and PM10) at a temporal resolution of 1 min. Likewise, maximum average values of concentrations of particulate material less than 1um, 2.5um and 10um were obtained, which can reach values of 40, 49, 55 μg/m3, respectively. It is concluded that the high values slightly exceed the environmental quality standards of Peru.